RELATIONSHIP OF MORINGA LEAF CONSUMPTION HABITS AND BLOOD SUGAR LEVEL IN MUNA TRIBE IN INDONESIA - Irma, Rita; Widianingsih, Emi; Rasmaniar, Rasmaniar (Public Health of Indonesia, 2020)
Background: In Indonesia, the prevalence of Diabetes Mellitus (DM) has increased. DM can have a significant impact on health that requires serious countermeasures. Moringa leaves have been extensively studied in terms of their efficacy in the treatment and prevention of DM.Objective: To identify the relationship between the habit of consuming Moringa leaves and blood sugar levels of Muna tribe.Method: This study was a cross-sectional study design conducted among local people in the Muna tribe community at Gunung Jati sub-district, Kendari, Southeast Sulawesi, Indonesia. A total of 81 people was participated selected using a proportional random sampling.Results: The average of frequency consumption of Moringa leaves among Muna tribe was one time a day, with consumption as much as 160 grams/day. The average of normal blood sugar was 103.5 mg/dl. There was no relationship between age, gender, education, working status with the frequency and amount of Moringa leaf intake. Similarly, analysis of blood sugar based on characteristics, there was no relationship between gender, education, working status with blood sugar, but there was a significant relationship between age and blood sugar (p=0.00). There was no relationship between the frequency and amount of moringa leaf intake with blood sugar levels.Conclusion: There was no relationship between the habit of consuming Moringa leaves both in terms of characteristics and blood sugar level among Muna people in the Gunung Jati, Kendari, Southeast Sulawesi, Indonesia.